PERILAKU CYBERLOAFING DITINJAU DARI KECERDASAN ADVERSITAS DAN KOMITMEN KERJA - Tri Rahayuningsih (LPPM Universitas Abdurrab, 2017)
This study aimed to determine the effect of intelligence adversity and work commitment to cyberloafing behavior of lecturer at the Asean Economic Community (MEA)’s era. So, this research beneficial to the development of theoretical science of industrial and organizational psychology about work behavior, as well as suggestions to keep the factors that make lecturer can avoid unproductive work habits that was cyberloafing, given the importance of the role of the faculty. This study used a quantitative method by spreading questionnaires to lecturers consisting of adversity intelligence scale, work commitment scale, and cyberloafing behavior scale that researchers collated by self, and analyzed statistically to discussed the cyberloafing behavior of lecturers. According to Lim (2002) cyberloafing an employee volunteer activities in the office, in using the internet access that has no correlation in the work. The result of this research showed that there is correlation between adversity intelligence and work commitment with cyberloafing behavior based on p value = 0,042 hence acceptable hypothesis, and contribution of adversity intelligence and work commitment equal to 19% to cyberloafing behavior. It is expected to be a suggestion for Higher Education to improve the quality of lecturer in facing MEA. Keywords: cyberloafing behavior, adversity intelligence, work commitment